Training, attitude change and paradigm shift : a case study of rural Iban community - Peter, Jambai (Universiti Malaysia Sarawak, (UNIMAS), 2003)
The main purpose of this study is to determine the relationship between training, attitude change and paradigm shift of the rural Iban community in Sarawak. The study was conducted in Mid-Layar Rural Growth Center, Betong, Sarawak